The Acceptability, Safety and Impact of a Play Co‐Developed With Public Contributors as a Format for Disseminating Research on a Sensitive Subject - Cat Papastavrou Brooks; Noreen Hopewell‐Kelly; Natalia V. Lewis (Health Expectations)
ABSTRACT Introduction Patient and public involvement (PPI) and dissemination of research findings are key parts of the pathway to research impact; however, traditional approaches often fail to engage non‐academic audiences. Creative methods such as co‐developed plays can be effective ways of making the research process and findings more engaging and accessible to the public. Not much is known about how to safely involve patients and the public in the development and delivery of plays disseminating research on sensitive subjects. Members of a PPI group on a study about mindfulness for women with a history of domestic abuse co‐developed and performed a play about their experiences. This study aimed to evaluate the impact, acceptability and safety of a co‐developed play in publicizing PPI and findings from research on domestic abuse. Methods We conducted a mixed‐methods study with the play team and audience. We collected 20 quantitative and 56 qualitative survey responses from audience members, carried out 4.25 h of direct observations of play performances and interviewed seven audience members and eight play team members. Data were analyzed using the framework method and descriptive statistics, using a ‘following a thread’ approach to integrate qualitative and quantitative findings in themes answering our study aim. Findings We developed three integrated themes with ten sub‐themes. The ‘Value’ theme summarized the plays' impact on audience understanding, potential mechanisms of impact and its effectiveness in depth over breadth of dissemination. The ‘Re‐traumatization’ theme described potential harms of the play, the risks of re‐traumatizing actors and distressing audiences. The ‘Reducing the risks’ theme summarized ways of reducing these risks of harm. Conclusion A play co‐developed and performed by study PPI members raised awareness of domestic abuse. However, there were divergent opinions on its value in disseminating messages about PPI in research on sensitive subjects. The value of the play for research dissemination was linked to its ability to emotionally engage the public, and to its accessibility. Implementing strategies to reduce the risk of re‐traumatizing audience members and the project team is recommended. Patient or Public Contribution Everyone with direct experience of co‐creating and performing the play contributed to this study. This included four public contributors: a community theatre producer, two actors with lived experience of domestic abuse who were members of the study PPI group and one community actor already working with the community theatre. A participatory workshop with PPI contributors was held to refine our research questions and data collection instruments, using a public involvement evaluation tool, The Cube. PPI contributors checked and commented on the draft manuscript.